Efektivitas Penggunaan Metode Thariqah Tasalsuli dalam meningkatkan Hafalan Al-Qur’an Program Studi Pendidikan Agama Islam Angkatan 2023 Fakultas Ilmu Tarbiyah dan Keguruan UIN Raden Fatah Palembang - Isdaria Mawarni; Alihan Satra; Karoma Karoma (Journal of Innovative and Creativity, 2025)
This study aims to maintain and improve the memorization of kalamullah by using a specific technique, namely the Thariqah Tasalsuli method. This research is a qualitative study with a descriptive approach. It uses two types of data sources: primary data obtained directly from interviews with the Program Coordinator, lecturers of the Islamic Education Study Program (PAI), and students; and secondary data in the form of documents. The researcher was directly involved in the field at the Islamic Education Study Program of UIN Raden Fatah Palembang to collect relevant data using observation, interviews, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing.The findings of this study on the effectiveness of the Thariqah Tasalsuli method in improving Qur'an memorization among students of the Islamic Education Study Program, class of 2023, Faculty of Tarbiyah and Teacher Training at UIN Raden Fatah Palembang, show that this method is effective in enhancing both the quality and quantity of Qur'an memorization. The method emphasizes memorizing verses in an orderly, sequential, and continuous manner from the beginning to the end of a surah, which strengthens memory, reduces the chance of forgetting, and builds systematic and consistent repetition.